Updated Brazilian database on food carotenoids: Factors affecting carotenoid composition - Rodriguez-Amaya, Delia B.; Kimura, Mieko [UNESP]; Godoy, Helena T.; Amaya-Farfan, Jaime (Academic Press Inc. Elsevier B.V., 2008)
This article updates the Brazilian database on food carotenoids. Emphasis is on carotenoids that have been demonstrated important to human health: alpha-carotene, beta-carotene, beta-cryptoxanthin, lycopene, lutein and zeaxanthin. The sampling and sample preparation strategies and the analytical methodology are presented. Possible sources of analytical errors, as well as the measures taken to avoid them, are discussed. Compositional variation due to such factors as variety/cultivar, stage of maturity, part of the plant utilized, climate or season and production technique are demonstrated. The effects of post-harvest handling, preparation, processing and storage of food on the carotenoid composition are also discussed. The importance of biodiversity is manifested by the variety of carotenoid sources and the higher levels of carotenoids in native, uncultivated or semi-cultivated fruits and vegetables in comparison to commercially produced crops. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: carotenoid; analysis; Composition; influencing factors; processing effects; health implications